Transformed Canine and Murine Mesenchymal Stem Cells as a Model for Sarcoma with Complex Genomics - Franceschini, Natasja (Cancers (Basel), 2021)
SIMPLE SUMMARY: Sarcomas are rare cancers of mesenchymal origin, the majority of which are characterized by many copy number alterations, amplifications, or deletions. Because of these complex genomics, it is notoriously difficult to identify driver events of malignant transformation. In this study, we show that murine and canine mesenchymal stem cells (MSCs) can be used to model spontaneous malignant transformation towards sarcomas with complex genomics. We show that these MSCs have an abnormal karyotype, many structural variants, and point mutations at whole genome sequencing analysis, and form sarcomas after injection into mice. Our cross-species analysis reveals that p53 loss is an early event in sarcomagenesis, and it was shown that MSCs with a knock-out in Trp53 transform earlier compared to wild-type MSCs. Our study points to the importance of p53 loss in the transformation process towards sarcomas with complex genomics. ABSTRACT: Sarcomas are rare mesenchymal tumors with a broad histological spectrum, but they can be divided into two groups based on molecular pathology: sarcomas with simple or complex genomics. Tumors with complex genomics can have aneuploidy and copy number gains and losses, which hampers the detection of early, initiating events in tumorigenesis. Often, no benign precursors are known, which is why good models are essential. The mesenchymal stem cell (MSC) is the presumed cell of origin of sarcoma. In this study, MSCs of murine and canine origin are used as a model to identify driver events for sarcomas with complex genomic alterations as they transform spontaneously after long-term culture. All transformed murine but not canine MSCs formed sarcomas after subcutaneous injection in mice. Using whole genome sequencing, spontaneously transformed murine and canine MSCs displayed a complex karyotype with aneuploidy, point mutations, structural variants, inter-chromosomal translocations, and copy number gains and losses. Cross-species analysis revealed that point mutations in Tp53/Trp53 are common in transformed murine and canine MSCs. Murine MSCs with a cre-recombinase induced deletion of exon 2–10 of Trp53 transformed earlier compared to wild-type murine MSCs, confirming the contribution of loss of p53 to spontaneous transformation. Our comparative approach using transformed murine and canine MSCs points to a crucial role for p53 loss in the formation of sarcomas with complex genomics.